Prevalence of Staphylococci Aureus nasal carrier in healthy school students in Gorgan - A.Tabbarai (M.Sc); E.Ghaemi (Ph . D); M.R.Fazeli (Ph.D); S.Bakhshandeh nosrat (M.D); N.Behnampour (M.Sc); M.Basori (B.S) (مجله دانشگاه علوم پزشکی گرگان, 2001)
Golden Staphylococci is one of the most common factors in skin and systemic infection. About 30% of people are carrying this bacterium in their skin and nose. Increased drug resistance in this microorganism and consequent infection, has gained the attention of scientific organization. Therefore we decided to determine the prevalence of nose carrier of this bacterium in healthy children in Gorgan schools. During the winter 1998 to March 1999 the sample has been taken from 1193 student’s nose with sterile cotton swab. These results showed that in 194 samples (16.3%) Staphylococci Aureus has been isolated, from these samples 114 cases belong to girls (16.1%) and 80 cases were boys (16.4%) that there is not a meaningful variation between them. The number of bacteria isolated from the villages children was 109 cases (17.6%) and in town’s children were 85 cases (14.8%), also this difference didn’t show significant difference. The prevalence of carrier among the 6-12 years old was 12-25.3%, which has got a significant meaning (P<0.001). Antibiotic resistance in the isolated S.aureus were tested and result showed that 34.8% of samples are resistant to Methicilin and 1.7% were resistant to Vancomycin, only 4% were sensitive to Penicillin. Therefore with regard to the results of this investigation, further researches are recommended in relation between strain’s of S.aureus that isolated from carrier’s and strain’s that isolated from patients and to determine their drug resistance in this region.